A Review on E-Commerce - Pandey, Dr. Shruti (JOURNAL OF BUSINESS MANAGEMENT & QUALITY ASSURANCE, 2022)
E-commerce is a boom in the modern business. E-commerce means electronic commerce. E- commerce (Electronic commerce) involves buying and selling of goods and services, or the Transmitting offunds or data, over an electronic network, predominantly the Internet. E-commerce (Electronic commerce) is a paradigm shift influencing both marketers and the Customers. Rather e-commerce is more than just another way to boost the existing business Practices. It is leading a complete change in traditional way of doing business. This significant change in business model is witnessing a tremendous growth around the globe and India is not an exception. A massive internet penetration has added to growth of E-commerce and more particularly start-ups have been increasingly using this option as a differentiating business model. Moreover E-Commerce has significant influences on the environment. Although the model is highly used in current business scenario but the option has not been explored at its fullest. The current research has been undertaken to describe the scenario of E-Commerce, analyze the trends of E-Commerce. The study further examines the key variables imperative for the success of E- commerce business models. Objective: The objectives of present study are: 1. To understand the present status and trends of E-Commerce and 2. To reveal the key variables influencing the increased usage of E-Commerce. Key Words: E-Commerce, Internet, Self-service, Technology, Internet banking.